The Protective HIV-1 Envelope gp41 Antigen P1 Acts as a Mucosal Adjuvant Stimulating the Innate Immunity - Xu, Lin; Tudor, Daniela; Bomsel, Morgane (Frontiers in Immunology, 2021)
Mucosal nasal vaccine development, although ideal to protect from pathogens invading mucosally, is limited by the lack of specific adjuvant. We recently used P1, a conserved region of HIV-1 gp41-envelope glycoprotein, as efficient antigen in a prophylactic HIV-1 mucosal vaccine applied nasally. P1 immunomodulation properties were assessed on human nasal mucosal models, by measuring induction of cytokine and chemokine production, intracellular signaling pathways, mucosal dendritic cells (DC) activation, and T-cell proliferation. P1 adjuvant properties were evaluated by quantification of antigen-specific B cell responses against a model antigen in an in vitro immunization model. We now demonstrated that P1 has additional immunological properties. P1 initiates immune responses by inducing nasal epithelial cells to secrete the Th2-cytokine Thymic Stromal Lymphopoietin (TSLP), a described mucosal adjuvant. Secreted TSLP activates, in turn, intracellular calcium flux and PAR-2-associated NFAT signaling pathway regulated by microRNA-4485. Thereafter, P1 induces mucosal dendritic cell maturation, secretion of TSLP in a TSLP- receptor-(R)-dependent autocrine loop, but also IL-6, IL-10, IL-8, CCL20, CCL22 and MMP-9, and proliferation of CD4+ T cells. Finally, P1 acts as an adjuvant to stimulate antigen-specific B cell responses in vitro. Overall, P1 is a multi-functional domain with various immuno-modulatory properties. In addition to being a protective vaccine antigen for HIV prevention, P1 acts as adjuvant for other mucosal vaccines able to stimulate humoral and cellular antigen-specific responses.